PENERAPAN PENDEKATAN TPACK DALAM MENINGKATKAN MINAT BELAJAR SEJARAH PADA PESERTA DIDIK KELAS XI IBB MAN 1 KOTA SEMARANG TAHUN 2022/2023 - Zenna Pramana (Universitas Negeri Semarang, 2025)
This classroom action research aimed to increase students' interest in learning history by implementing the TPACK approach in Grade XI IBB at MAN 1 Kota Semarang. The study's objectives were to describe the process of applying the TPACK approach and to assess its effectiveness in enhancing students' interest in history during the 2022/2023 academic year. The research design was a collaborative Classroom Action Research (CAR), involving Grade XI IBB students. Data collection techniques included questionnaires, tests, documentation, and observations, conducted over two cycles, each consisting of planning, implementation, observation, and reflection stages. The study's findings indicated that applying the TPACK approach significantly improved students' engagement and learning outcomes in history. In the first cycle, student participation was limited, and not all students achieved the learning completeness standard. However, in the second cycle, there was a notable improvement in both student engagement and learning outcomes, with all students meeting the learning completeness criteria. The success of the TPACK approach was evidenced by a 74% increase in student interest and an average class score of 88. Despite the improvement, active student involvement during the learning process remained an area for further enhancement.